RNA interference mediated suppression of TRPV6 inhibits the progression of prostate cancer in vitro by modulating cathepsin B and MMP9 expression - Kim, Duk Yoon; Kim, Soon Hee; Yang, Eun Kyoung (Investigative and clinical urology, 2021)
The transient receptor potential vanilloid 6 (TRPV6) channel is overexpressed in prostate cancer and its silencing is known to inhibit the growth of LNCaP cells. However, the role of TRPV6 in the metastasis of prostate cancer cells and its relationship to the invasive markers, matrix metalloproteinase (MMP) and cathepsin B, is unclear. Thus, the present study was focused on understanding these tumor-related processes. We performed a wound-healing assay and a Transwell migration and invasion assay to assess the migration and invasion of prostate cancer cells. Western blot analysis was used to measure the expression of cathepsin B, MMP2, and MMP9. TRPV6 siRNA significantly inhibited the proliferation of LNCaP prostate cancer cells. It also significantly attenuated the wound healing and migration capacities of LNCaP cells. Moreover, the invasiveness of LNCaP cells and the expression of MMP9 and cathepsin B in LNCaP cells were also significantly inhibited by TRPV6 siRNA. The results indicate that TRPV6 may promote prostate cancer progression in association with MMP9 and cathepsin B, thereby validating further research into TRPV6 as a useful therapeutic target for local invasion or metastasis of advanced prostate cancer.